Biophilic, Ethical, and Low-Carbon Design Integration in Visual Communication for Social Media Campaigns - Jin, Park Soo; Eun, Jeong Ji; Ho, Seo Kang (University of Science and Computer Technology, 2025)
This study aims to develop an integrative model that unites biophilic aesthetics, ethical storytelling, and low-carbon design strategies into a single sustainable framework for digital communication. Using a qualitative multi-case approach, the research draws on semi-structured interviews with six expert designers and content analysis of ten social media campaigns selected for their ecological or ethical orientation. The analysis applied thematic coding and visual evaluation to identify recurring patterns and design challenges. Findings show that while nature-inspired and ethically grounded visuals are increasingly employed to foster emotional connection and inclusivity, explicit low-carbon design practices remain rare due to limited awareness and measurement tools. The study introduces a practical framework linking environmental psychology, design ethics, and digital sustainability. Its novelty lies in demonstrating that aesthetic engagement and ecological responsibility.